Optimization of industrial power-supply system during its reconstruction - Тимчук, Сергей Александрович; Деренько, Николай Семенович (Eastern-European Journal of Enterprise Technologies, 2013)
As a result of economic situation changes a problem of selecting the optimal solution for industrial enterprise power-supply system reconstruction has appeared. The solution is complicated by multicriteriality, vagueness of source information, nonlinearity and relatively great number of alternatives. The vagueness of source information is solved by developing a fuzzy mathematical model of technical and economic evaluation of power-supply system efficiency indexes, which are used as objective functions. Genetic algorithm has been applied for selecting optimal solutions. The research has been carried out by the example of power-supply system of a particular enterprise. As a result, three optimal solutions for different levels of capital costs have been developed. The first solution allows electric power technological losses reduction and safety increase by 5 times, although it requires additional investments. The second solution allows electric power technological losses reduction by 5.8 times and safety increase by 2.3 times, herewith capital costs may be partially compensated by selling released equipment. The third solution ensures electric power technological losses reduction by 4.1 times and safety increase by 2.3 times without additional capital costs. The third variant is more preferable for the example considered. Fuzzy values of technical and economic indexes for optimal solutions allow assessing the risks of decision-taking.